EFFECT OF MYCORRHIZAE AND WOOD VINEGAR ON THE SEEDLINGS GROWTH OF FIVE PROVENANCES OF Paraserianthes falcataria - Mohamad Siarudin; Endah Suhaendah (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2007)
The objective of the study was to increase the growth of 5 provenances albizia (Paraserianthes falcataria L. Nielsen) in the nursery. The experimental design was Split Plot Design, with 5 provenances of albizia as main plot and 3 treatment (wood vinegar application, mychorrizae application and control) as sub plot. Each sub plot consited of 45 seeds as sample,. Growth parameter observed was delta height: that is different beetween measurement at the early application (3 weeks age of seedling ) and at the last measurement (10 weeks age of seedling). The data obtained then analyzed by using analysis of variance of continued with Duncan test. The result showed that mychorrizae and wood vinegar application have significant effect on the growth of albazia seedling. The best performance was shown at wood vinegar application (height average 75,48 cm and height delta 66,62 cm), mychorrizae application (height average 66,44 cm and height delta 59,22 cm) and control (height average 58, 92 cm and height delta 52, 48 cm) respectively. Provenance differences were also significant. The best performance were shown at provenance of Candiroto, Kediri, Ciamis, Wamena dan Subang. Height delta each provenance after 7 weeks application were 67,65 cm, 62,93 cm, 60,15 cm 53,37 cm dan 53,11 cm; while the total height at the 10 weeks age of seedling were 74,44 cm, 69,33 cm, 69,14 cm, 61,02 cm dan 60,80 cm respectively.